SCRAPING WEB MARKETPLACE MENGGUNAKAN METODE DOM PARSING UNTUK PENGUMPULAN DATA PRODUK - Muhammad Joko Umbaran Haris Bahrudin; Hardan Gutama (Teknik Informatika, 2020)
Web Scraper is a way of extracting scripts that run there that are commonly chosen to do web memos via DOM parsing. Specific nodes that are collected using DOM parsers and tools like XPath help the process of scraping web pages. In this study using the DOM Parsing method to obtain product data on the market. Sraper can be further developed as a data collection technique on the internet for further research that can be provided about the concept of big data to be used for forecasting or getting the information needed. Alone Parsing is a way of breaking data or symbols, both in language and in language, according to formal grammar rules. After using the parshing technique, it will be generated again using Parse Tree, which is a process of compiling product data that forms like a tree, using siyntak analysis to break down product categories.